OCCUPATIONAL HEALTH AND SAFETY ANALYSIS IN THE CATTLE SLAUGHTERING PROCESS AT THE SLAUGHTERHOUSE IN DENPASAR CITY - Pereira, Joanita Auxilia de Sa; Agustina, Kadek Karang; Suada, I Ketut (Buletin Veteriner Udayana, 2026)
The cattle slaughtering process at the Slaughterhouse (RPH) involves various occupational health and safety (OHS) hazards that require effective management. This study aims to identify potential OHS hazards and assess their risk levels at each stage of the cattle slaughtering process at the Denpasar City RPH. The research method used an observational approach with the Hazard Identification and Risk Assessment (HIRA) technique to analyze physical, biological, ergonomic, and psychosocial hazards. The results show that several work stages have a high-risk level (score ≥10), particularly during the <strong style="font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; text-align: start; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; word-spacing: 0px;">slaughtering stage<span style="font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; text-align: start; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; word-spacing: 0px;"> (physical risk score 10, biological score 12, ergonomic score 12) and the <strong style="font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; text-align: start; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; word-spacing: 0px;">use of the restraining pen<span style="font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; text-align: start; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; word-spacing: 0px;"> (physical risk score 16). Dominant hazards include exposure to zoonotic bacteria, injuries from sharp tools and animals, and musculoskeletal disorders due to non-ergonomic working postures. Psychosocial factors such as work stress also contributed significantly, with risk scores reaching 12 in several stages. Based on these findings, this study recommends implementing comprehensive mitigation measures, including: (1) improved use of standardized personal protective equipment (PPE), (2) regular OHS training on animal handling and tool use, (3) redesign of work facilities to be more ergonomic, (4) implementation of an ISO 45001-based OHS management system, and (5) a mental health program for workers. These recommendations are expected to reduce work accident rates and increase productivity at the Denpasar City RPH, while also serving as a reference for developing OHS policies in the livestock sector.